Teaching Science Using Flipped Learning To Support Students In Inclusion Classes And Its Impact On Achievement And Self-Efficacy (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to investigate the effectiveness of teaching science using flipped learning to support students in inclusion classes and its impact on achievement and self-efficacy. An assessment of self-efficacy in the scientific field was created using the experimental technique with a quasi-experimental design. The sample in this study included (100) students; (50) students from Abu Bakr Al-Siddiq school in Jordan and (50) fifth-grade students from Medina in Saudi Arabia. Each school had two groups, the first was an experimental group consisting of (25) students, and the second was a control group consisting of (25) students. The study's findings indicated favorable outcomes for the experimental group in the post-achievement exam for the two samples. The results showed that the post-self-efficacy test results for the two samples showed statistically significant differences, favoring the experimental group. The results revealed no variations between the two samples from the two schools.